1989
DOI: 10.1111/j.1540-5915.1989.tb01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Contrasting Formulations of Expectancy Theory*

Abstract: The explanatory potential of four forms of expectancy theory with additive and multiplicative expectancy terms and linear and nonlinear valence functions were contrasted. A behavioral decision-making theory approach was used when 101 subjects were asked to make 128 hypothetical job-choice decisions. More than 25,800 decisions under a within-subjects framework were analyzed. Results indicate that the majority (83 percent) of subjects employed additive or multiplicative expectancy models with linear valence func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In the current study, survivor typology (Spreitzer & Mishra, 2002), psychology (Deci, 1971;Moller et al, 2006), and stress (Lazarus, 1993) literatures served as the theoretical rationale for our proposed cynicism-job insecurity association. Equally plausible is an inclusion of expectancy theory (Vroom, 1964;Waldman & Spangler, 1989), which describes the process individuals undertake to choose appropriate behaviors when faced with alternatives (Baker, Ravichandran, & Randall, 1989). For example, insecure layoff survivors may find that maximizing their effort may be the best way to secure favorable outcomes, subsequently leading to job continuance.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, survivor typology (Spreitzer & Mishra, 2002), psychology (Deci, 1971;Moller et al, 2006), and stress (Lazarus, 1993) literatures served as the theoretical rationale for our proposed cynicism-job insecurity association. Equally plausible is an inclusion of expectancy theory (Vroom, 1964;Waldman & Spangler, 1989), which describes the process individuals undertake to choose appropriate behaviors when faced with alternatives (Baker, Ravichandran, & Randall, 1989). For example, insecure layoff survivors may find that maximizing their effort may be the best way to secure favorable outcomes, subsequently leading to job continuance.…”
Section: Discussionmentioning
confidence: 99%
“…This theory continues to be used in a variety of contexts to provide an explanation of an individual's behavioral intentions (e.g., [4] [21] [36] [47]). Expectancy theory proposes that individuals will exert effort to do those things that are expected to lead to outcomes that they value, or find attractive; the theory has often been referred to as an expectancy-value theory.…”
Section: Expectancy Theorymentioning
confidence: 99%
“…Cohen and Cohen (1975) have suggested that such a non-linear, utility-type relationship may be modelled with a squared valence term in either the additive or multiplicative formulations (V 2 j + E ij or V 2 j × E ij ). Other empirical research investigating the validity of expectancy theory as a model of employee motivation includes that by Baker et al (1989), Behling and Starke (1973), Liddell and Solomon (1977), Peters (1977), Stahl and Harrell (1981), Wahba and House (1974).…”
Section: Vroom's Expectancy Theorymentioning
confidence: 99%